Digital Transformation in Counseling Services: Ethical, Relational, and Sociocultural Perspectives on Technology-Based Counseling - Nurul Hidayatul Ulum; Elisa Br Ginting; Anis Tri Yuliana (Vokatek: Jurnal Pengabdian Masyarakat, 2026)
This study examines the transformation of counseling services in the digital era by exploring the ethical, relational, professional, and sociocultural dimensions of technology-based counseling. Using an integrative literature review approach, the study critically analyzes contemporary literature related to digital counseling, online therapy, telecounseling, and technology-mediated psychological support services. The analysis employs thematic content analysis to identify major conceptual patterns concerning therapeutic relationships, ethical adaptation, counselor competencies, accessibility, and sociocultural challenges within digitally mediated counseling environments. The findings indicate that digital counseling should not be understood merely as the transfer of conventional counseling into virtual platforms, but as a multidimensional sociotechnical transformation that reconstructs counseling practice within contemporary digital society. Technology-based counseling expands accessibility, flexibility, and inclusivity of psychological services while simultaneously generating ethical challenges related to cybersecurity, privacy protection, professional boundaries, and digital inequality. The study further reveals that therapeutic effectiveness in online counseling depends significantly on counselors’ ability to establish psychological presence, emotional responsiveness, and relational authenticity despite technological limitations. In addition, the implementation of digital counseling in developing countries such as Indonesia remains strongly influenced by sociocultural context, institutional readiness, and unequal digital infrastructure. This study proposes the concept of digital counseling as a humanistic sociotechnical ecosystem integrating technological innovation, ethical responsibility, relational engagement, and cultural sensitivity within contemporary counseling practice.